Collective bargaining with special reference to the law of Germany and Republic of Serbia - Misailović Jovana M. (Strani pravni život, 2019)
Collective bargaining is type of dialogue between social partners (representative trade unions and representative employer organization) which lead to conclusion of collective agreement. For success of collective bargaining, it must necessarily be laid on a democratic basis and it must be in accordance with appropriate legal framework that enables the social partners to act autonomously and independently. This means that employees, on the one hand, and employers, on the other, have the right to freely choose to form their own organizations (trade unions and employers' organizations), and to join them under the conditions prescribed by their own statutes or rules. The author considers right to collective bargaining as one of the cornerstone rights adopted by International Labour Organisation and give a special attention to legal framework and situation regarding collective bargaining in Germany and Republic of Serbia.